2009
DOI: 10.1113/jphysiol.2008.164970
|View full text |Cite
|
Sign up to set email alerts
|

The cystic fibrosis transmembrane conductance regulator in reproductive health and disease

Abstract: The cystic fibrosis transmembrane conductance regulator (CFTR) is an anion channel regulated by cAMP-dependent phosphorylation, which is expressed in epithelial cells of a wide variety of tissues including the reproductive tracts. Mutations in the gene encoding CFTR cause cystic fibrosis, a common genetic disease in Caucasian populations with a multitude of clinical manifestations including infertility/subfertility in both sexes. However, the physiological role of CFTR in reproduction and its involvement in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
101
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 111 publications
(105 citation statements)
references
References 63 publications
3
101
1
Order By: Relevance
“…Furthermore, CFTR is also known to be involved in bicarbonate transport either directly [53] or indirectly [54], which is important for activation of cAMPdependent signaling pathway [53,55] in addition to pH regulation. In the last decade, various studies from our laboratory have demonstrated that normal function of CFTR and/or ENaC is critical for a variety of reproductive events such as sperm capacitation [53,56] and implantation [57,58], defects or dysregulation of which lead to a number of pathological conditions, such as ovarian hyperstimulation syndromes, hydrosalpinx and infertility [44,59]. These observations suggest that ion channels/transporters may respond to microenvironmental changes and play an important role in various physiological and pathological processes.…”
Section: Ion Channels/transporters and Their Crosstalk With The Micromentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, CFTR is also known to be involved in bicarbonate transport either directly [53] or indirectly [54], which is important for activation of cAMPdependent signaling pathway [53,55] in addition to pH regulation. In the last decade, various studies from our laboratory have demonstrated that normal function of CFTR and/or ENaC is critical for a variety of reproductive events such as sperm capacitation [53,56] and implantation [57,58], defects or dysregulation of which lead to a number of pathological conditions, such as ovarian hyperstimulation syndromes, hydrosalpinx and infertility [44,59]. These observations suggest that ion channels/transporters may respond to microenvironmental changes and play an important role in various physiological and pathological processes.…”
Section: Ion Channels/transporters and Their Crosstalk With The Micromentioning
confidence: 99%
“…In the context of reproductive tract, an optimal fluid microenvironment is considered to be crucial for successful reproductive events occurring along the genital tract, such as sperm capacitation, fertilization, embryo development and implantation [43,44]. For instance, during blastocyst implantation, the volume and composition of uterine fluid have been reported to undergo significant changes to facilitate blastocyst attachment and embedding [45].…”
Section: Ion Channels/transporters and Their Crosstalk With The Micromentioning
confidence: 99%
“…Generally speaking, infertility in females with CF has a less serious outcome than in males and is thought to be due to thickening of cervical mucus [26].…”
Section: Pancreas and Gi Tractmentioning
confidence: 99%
“…CFTR is a cAMP-activated ATP-gated anion channel that transports chloride and thiocyanate ions across epithelial cell membranes. Any defect in CFTR expression and function may lead to various pathological conditions, especially chronic in ammatory diseases [10][11][12][13][14]. Some studies have con rmed the role of CFTR in chronic lung infections with mucoid Pseudomonas aeruginosa [11,12], while other studies have demonstrated that variations of CFTR gene may increase or decrease the risk of a variety of in ammation-associated cancers, including lung cancer and pancreatic cancer [13][14].…”
mentioning
confidence: 99%